Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-68 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Foot arches during supported walking. Note the right foot has in the stance phase (A, arrow) no foot arch.